PENERAPAAN KURIKULUM 2013 PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Ira Rahmayuni Jusar; Nurhizrah Gistituati; Alwen Bentri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The application of the 2013 curriculum to mathematics learning in elementary schools still has polemics even though it has changed to an independent curriculum. Applying the 2013 curriculum to mathematics learning in elementary schools has dynamics for students and teachers. Applying the 2013 curriculum to mathematics learning in elementary schools explains the success of teachers in developing syllabuses and lesson plans in the classroom. Applying the 2013 curriculum to mathematics learning in elementary schools affects the policy of government in regulating, and the implementation of the 2013 curriculum is well-socialized to teachers and students. The study used a literature study collected from ten journal reviews based on learning objectives on the 2013 curriculum by meta-analysis. The results showed that the application of the 2013 curriculum to mathematics learning in elementary schools had been carried out well, such as the planning of mathematics learning, the implementation of mathematics learning, the evaluation of learning processes and learning outcomes based on the 2013 curriculum. The 2013 curriculum process standards and the procedure for implementing the 2013 curriculum standards include an introduction, core activities, and closings, although there are obstacles in the distribution of student books and teacher books and the difficulty of teachers in understanding the creation of shiva worksheets.